c-Jun as a one-way valve at the naive to primed interface - Dongwei Li; Ling Luo; Lin Guo; Chuman Wu; Ran Zhang; Yuling Peng; Menghua Wu; Junqi Kuang; Yan Li; Yudan Zhang; Jun Xie; Wenxiu Xie; et al. (Cell & Bioscience, 2023)
Abstract Background c-Jun is a proto-oncogene functioning as a transcription factor to activate gene expression under many physiological and pathological conditions, particularly in somatic cells. However, its role in early embryonic development remains unknown. Results Here, we show that c-Jun acts as a one-way valve to preserve the primed state and impair reversion to the naïve state. c-Jun is induced during the naive to primed transition, and it works to stabilize the chromatin structure and inhibit the reverse transition. Loss of c-Jun has surprisingly little effect on the naïve to primed transition, and no phenotypic effect on primed cells, however, in primed cells the loss of c-Jun leads to a failure to correctly close naïve-specific enhancers. When the primed cells are induced to reprogram to a naïve state, these enhancers are more rapidly activated when c-Jun is lost or impaired, and the conversion is more efficient. Conclusions The results of this study indicate that c-Jun can function as a chromatin stabilizer in primed EpiSCs, to maintain the epigenetic cell type state and act as a one-way valve for cell fate conversions.